The Innermore Ossein- Enchondroma - Bajaj Anubha (Journal of Clinical and Diagnostic Pathology, 2021)
Preface Frequently, benign bone tumours are an incidental discovery wherein clinical symptoms are contingent to tumour location and magnitude and manifest as localized pain, swelling, skeletal deformities or pathologic fracture. Radiographic imaging is a cogent methodology of discerning the neoplasms.
Keywords: enchondroma